Improving NGSS focused model-based learning curriculum through the examination of students’ experiences and iterated models - Park, Byung-Yeol; Campbell, Todd; Kelly, Miriah Russo; Gray, Ron; Arnold, Chester; Chadwick, Cary; Cisneros, Laura M.; Dickson, David; Moss, David M.; Rodriguez, Laura; Volin, John C.; Willig, Michael R. (Research in Science & Technological Education, 2021)
Background: It is crucial to support students in better understanding water and sustainability issues because water plays a vital role in maintaining global ecosystems, including human life. A wide range of curricular and instructional supports like those embodied in model-based learning (MBL) are necessary for teachers to engage students in the core epistemic commitments of the Next-Generation Science Standards (NGSS). Purpose: The main purpose of this study is to inform theory about students’ early attempts to engage in the complex kinds of sensemaking experiences inherent in the Framework for K-12 Science Education and the NGSS. Sample: Data for this study was collected from 74 10th grade students in a high school in the Northwest region of the New England state. Design and Methods: An explanatory sequential mixed-method research design was used to examine students’ learning outcomes, and to better understand these outcomes in connection to their experiences engaging in modeling in the MBL curriculum unit. Results: The results indicated that students’ model scores, the number of concepts in models, and the coherence and sophistication of models improved between their initial and final models. Additionally, the following patterns emerged related to ways in which students engaged in the practice of modeling: (1) students attempted to directly represent what they observed, (2) they struggled to pictorially express complex patterns or mechanisms, and (3) students experienced difficulties representing models from a diverse range of perspectives. Conclusion: The patterns identified across student models, as well as their reports of experiences related to the MBL unit implementation, provided insight into student experiences with models, while also providing meaningful implications for the refinement of the MBL curriculum unit investigated in this research specifically, while informing approaches MBL curricular units aimed at supporting NGSS implementation efforts more generally. © 2021 Informa UK Limited, trading as Taylor & Francis Group.
Keywords: dept.egm; peer-reviewed

Who responds to health, environmental, and economic information about local food? Evidence from Connecticut seafood consumers - Tian, Yixing; Croog, Rose; Bovay, John; Concepcion, Anoushka; Getchis, Tessa; Kelly, Miriah Russo (Aquaculture Economics & Management, 2021)
We designed and implemented a discrete choice experiment to assess how information about the health, environmental, and economic benefits of locally produced aquaculture products affect Connecticut consumers’ willingness to pay (WTP) for products produced in the state, as compared with products from another state or another country. We find that information about local economic benefits tended to increase WTP for Connecticut-grown and -raised products, whereas information about health, safety, and the environment tended to decrease WTP for products from other regions. We also explore heterogeneous effects of the information treatments by respondent gender, education, and income. © 2021 Taylor & Francis Group, LLC.
Keywords: dept.egm; peer-reviewed

Temperature-dependent effects on fecundity in a serial broadcast spawning fish after whole-life high CO2 exposure - Concannon, Callie A; Cross, Emma L.; Jones, Lucas F; Murray, Christopher S.; Matassa, Catherine M.; McBride, Richard S.; Baumann, Hannes (ICES Journal of Marine Science, 2021)
Keywords: dept.egm; peer-reviewed

Enacting a just and sustainable blue economy through transdisciplinary action research - Heidkamp, C. Patrick; Garland, Michaela; Krak, Louie (The Geographical Journal, 2021)
To enact a just and sustainable blue economy, one must consider all the actors involved in its shaping. This paper argues that a quintuple helix approach to stakeholder engagement – involving government, academia, the business community, and civil society – and an inclusive transdisciplinary action research (TAR) methodology are promising avenues with which to do so. Embracing critical pragmatism as a foundational framework, key ideas from three strands of research are consolidated: (1) the recent work on the geographical dimension of socio-technical sustainability transitions; (2) the literature on just sustainabilities and just transition; and (3) action research and transdisciplinary approaches to problem solving. This allows for the reimagination of a common future for the blue economy that is developed through a different kind of democratic process driven and informed by co-learning, and shared experiences. By adopting a transdisciplinary action research approach, actors from different disciplines and spheres of experience can gain a better mutual understanding and find commonality through the open door of collaboration. The theoretical argument presented in this paper is illustrated by a vignette of an ongoing TAR project at Southern Connecticut State University, which outlines the challenges and opportunities inherent to implementing a TAR approach. The information, practices and views in this article are those of the author(s) and do not necessarily reflect the opinion of the Royal Geographical Society (with IBG). © 2021 The Authors. The Geographical Journal published by John Wiley & Sons Ltd on behalf of Royal Geographical Society (with the Institute of British Geographers)
Keywords: dept.egm; peer-reviewed

Metabolic response to temperature stress in the Colombian freshwater crab Neostrengeria macropa (H. Milne Edwards, 1853) (Decapoda: Brachyura: Pseudothelphusidae) - Hudson, D.M. (Journal of Crustacean Biology, 2021)
Freshwater crustaceans are distributed throughout the montane and lowland areas of Colombia, and are therefore a useful indicator group for how aquatic species will respond to climate change. As such, metabolic determination of physiological performance was evaluated for the Colombian pseudothelphusid crab, Neostrengeria macropa (H. Milne Edwards, 1853), over a temperature range inclusive of current temperatures and those predicted by future scenarios in the plateau around the city of Bogotá, namely from 8 °C to 30 °C. The performance results mostly aligned with previous exploratory behavioral determination of the ideal temperature range in the same species, although the metabolism increased at the highest temperature treatments, a point when exploratory behavior declined. These results indicate that this species of montane crab behaviorally compensates for increased thermal stress by decreasing its physical activity, which could have negative predator-prey consequences with changes to community structure as different species undergo climate-mediated geographic range shifts in the region. As this species is endemic to the plateau surrounding Bogotá, it also experiences a number of other stressors to its survival, including infrastructure development and invasive species. © 2021 The Author(s) 2021. Published by Oxford University Press on behalf of The Crustacean Society. All rights reserved. For permissions, please e-mail: journals.permissions@oup.com.
Keywords: dept.egm; peer-reviewed

Assessing the resiliency of salt marshes under increasing nitrogen loading - Crosby, Sarah C.; Spiller, Nicole C.; Healy, Devan S.; Brideau, Lauren; Stewart, Luke M.; Vaudrey, Jamie M.P.; Tietz, Kasey E.; Fraboni, Peter J. (Estuaries and Coasts, 2021)
Understanding the threat to ecosystems from excess nitrogen in coastal waters is a priority issue in scientific research and natural resource management. Previous field studies have demonstrated that high nitrogen loading can decrease the health and resiliency of salt marshes through shifting biomass allocation, increasing decomposition, and causing creek bank instability, all of which can lead to increased marsh loss with sea-level rise. However, other studies have shown relatively little impact of increasing nitrogen on the structure and function of these systems. Due to the long history of eutrophication in Long Island Sound, aggressive nitrogen reduction strategies have been enacted in this region, but detrimental nutrient inputs persist at variable levels throughout the watershed. Here, the extent of nitrogen-linked salt marsh change under varying levels of nutrient stress was measured, testing the hypothesis that salt marsh resilience (as measured by Spartina alterniflora belowground biomass and marsh edge stability) decreases with increasing nitrogen loading. S. alterniflora growth (stem height, stem density, and biomass) and within-marsh creek area were quantified in 10 salt marshes along a nitrogen-loading gradient. Increasing nitrogen loading showed a significant negative relationship with dead belowground biomass in S. alterniflora; the loss of this belowground biomass in higher nitrogen systems may decrease salt marshes’ ability to keep pace with sea-level rise. Neither shifts in live biomass allocation nor a positive relationship between aboveground biomass or stem height and increasing nitrogen was observed that might promote additional sediment capture, but higher stem density could play a role in promoting sedimentation on the marsh surface in more sediment-rich systems. Aerial photography analysis revealed marsh creek expansion since 1934 at 90% of the marshes studied, but unlike findings from prior experimental enrichment studies, the rate of marsh loss did not increase with increasing nitrogen loading. Given the importance of these ecosystems and the potential of nitrogen to decrease their resiliency, understanding the impacts of eutrophication on salt marshes is critical. However, these results show that the relative importance of nitrogen in driving salt marsh loss in Long Island Sound may be less than studies from other regions have suggested. © 2021, Coastal and Estuarine Research Federation.
Keywords: Spartina alterniflora; dept.egm; peer-reviewed